그린 레이저 포인터에 의한 황반부 손상 1예 - 김마르다, 권지원, 한영근Martha Kim M.D. Ji Won Kwon M.D. Young Keun Han M.D (Daihan angwa haghoi jabji, 2008)
목적 : 그린 레이저 포인터로 인한 황반부 손상 1예를 보고하고자 한다 증례 요약 : 내원 2년 전 천문관측용 그린 레이저 포인터를 1~2초 정도 실수로 주시한 후 우안의 급격한 시력감소가 있었던 25세 남자가 경과 관찰을 위하여 본원 안과에 내원하였다. 내원 당시 우안의 나안시력 및 최대교정시력은 안전수지였으며 안저검사 및 빛간섭단층촬영에서 황반부의 망막열공 및 반흔이 관찰되었다. 결론 : 그린 레이저 포인터의 빔을 1~2초 정도의 짧은 시간 주시하는 것만으로 황반 중심부의 손상을 입어 회복 불능의 시력 저하를 일으킨 증례를 보고하는 바이다. Purpose: We report a case of macular injury by accidental exposure to a green laser pointer. Case summary: A 25-year-old man had an acute reduction of visual acuity in his right eye two years ago after accidental exposure to a green laser pointer for a few seconds. The patient’s best corrected visual acuity was counting fingers in his right eye. Fundus examination and optical coherence tomography showed a macular hole and a linear retinal scar in his right eye. Conclusions: Green laser pointers may cause macular damage after exposure of just a few seconds, which can lead to irreversible reduction of visual acuity. KCI Citation Count: 3